On the solutions of a coupled system of proportional fractional differential inclusions of Hilfer type - Cernea, Aurelian (Modern Mathematical Methods, 2024)
A multi-point and integro-multi-strip boundary value problem associated to a Hilfer type coupled system of fractional differential inclusions is studied. The existence of solutions is established in the case when the set-valued maps has nonconvex values.